Cystic Fibrosis of the Pancreas: The Role of CFTR Channel in the Regulation of Intracellular Ca2+ Signaling and Mitochondrial Function in the Exocrine Pancreas - Madácsy, Tamara; Pallagi, Petra; Maleth, Jozsef (Frontiers in Physiology, 2018)
Cystic fibrosis (CF) is the most common genetic disorder that causes a significant damage in secretory epithelial cells due to the defective ion flux across the cystic fibrosis transmembrane conductance regulator (CFTR) Cl- channel. Pancreas is one of the organs most frequently damaged by the disease leading to pancreatic insufficiency, abdominal pain and an increased risk of acute pancreatitis in CF patients causing a significant decrease in the quality of life. CFTR plays a central role in the pancreatic ductal secretory functions by carrying Cl- and HCO3- ions across the apical membrane. Therefore pathophysiological studies in CF mostly focused on the effects of impaired ion secretion by pancreatic ductal epithelial cells leading to exocrine pancreatic damage. However, several studies indicated that CFTR has a central role in the regulation of intracellular signaling processes and is now more widely considered as a signaling hub in epithelial cells. In contrast, elevated intracellular Ca2+ level was observed in the lack of functional CFTR in different cell types including airway epithelial cells. In addition, impaired CFTR expression has been correlated with damaged mitochondrial function in epithelial cells. These alterations of intracellular signaling in CF are not well characterized in the exocrine pancreas yet. Therefore in this review we would like to summarize the complex role of CFTR in the exocrine pancreas with a special focus on the intracellular signaling and mitochondrial function.